Business Process Reengineering pada Coffee Shop Coffee Secret’s Menggunakan Aplikasi Dolibarr - Dian Paramitha Ida Ayu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Coffee Secret's is a coffee shop located in Denpasar City. Coffee Secret's often encounters obstacles in every business process. The problems experienced by Coffee Secret's are manual recording of incoming and outgoing raw materials, misuse of raw materials, wrong and excessive purchases of raw materials causing expired raw materials because they are not used up. The solution given is to do Business Process Reengineering (BPR) with the concept of Enterprise Resource Planning (ERP) and perform performance analysis using the Performance Prism and Analytical Hierarchy Process (AHP) and Key Performance Indicators (KPI) methods. KPI performance appraisal refers to the Performance Prism facet which involves all stakeholders in the company, namely owner stakeholders, customers, employees, suppliers and the surrounding community. The application of the proposed business process at Coffee Secret's is implemented using an ERP application, namely Dolibarr. Implementation with the Dolibarr application was tested using the User Acceptance Test (UAT) method. The results of the test using the UAT method have a score of 400 indicating that the application using the Dolibarr application is successful.